Rapid Climate Adaption Assessment (RCAA) of water supply and sanitation services in two coastal urban poor communities in Accra, Ghana - Clemenz, Nikolaus; Boakye, Richard; Parker, Alison (IWA Publishing, 2019)
This study assessed the impact of different hydrological scenarios on existing vulnerabilities of water and sanitation services in Chorkor and Shiabu, two coastal urban poor communities in Accra, Ghana. The hydrological scenarios were developed from the literature on climate change projections. This paper recommends adaptations for community members, service providers, and the municipality based on the impact assessment. Chorkor and Shiabu are vulnerable to an increase in rainfall because of the lack of adequate solid waste management and hydrological sound drains. Shiabu's topography and the indiscriminate sand mining along its beach make it vulnerable to an increase in sea level. Looking beyond Chorkor and Shiabu's community boundaries, the urban water utility which supplies water vendors in both communities may be severely impacted by a decrease in rainfall, which would lead to water scarcity and a shortage in hydroelectricity. Regardless of which climate change scenario emerges, many of the recommended adaptations are good water management practice, for example, increasing the number of household connections and reducing non-revenue water. Putting climate change high on the agenda has the potential to generate additional funding to help address Chorkor and Shiabu's water and sanitation problems, and climate-proof services for the future. However, the study method does not address the governance of these adaptations.
Keywords: Accra; climate change adaptation; climate change impacts; Ghana; sanitation; urban poor